„Lajki” i „hejty”, czyli kilka słów o socjolekcie polskich i rosyjskich użytkowników internetu - Kuligowska, Katarzyna (Studia Rossica Posnaniensia, 2016)
The author presents several psycho- and sociolinguistic phenomena connected with Internet use. An analysis of the sociolect of Polish and Russian Internet users allows the author to establish the main kinds of human activity in the Internet and what the impact that using the Internet has on the individual.